Critical considerations for fast and accurate regiospecific analysis of triacylglycerols using quantitative ¹³C NMR - Chuah, C.H.; Gouk, S.W.; Cheng, S.F.; Malon, M.; Ong, A.S.H. (Royal Society of Chemistry, 2013)
Quantitative ¹³C NMR (qCNMR) has been used as an appealing methodology for regiospecific analysis of triacylglycerols in edible oils and fats. It has advantages of shorter analysis time, precision and accuracy over laborious conventional Grignard or enzymatic hydrolysis method. Previous reported studies have recommended diversified NMR acquisition and processing parameters for the same quantification work. Different quantitative data were obtained by using a distinct sets of NMR parameters. To overcome this problem, we conducted a systematic investigation to examine the role of each acquisition and processing parameters to obtain high accuracy and repeatability data. Principal acquisition parameters, for instance pulse flip angle, repetition delay and temperature were investigated to correlate the targeted accuracies and practical experimental conditions. New data on spin-lattice relaxation times (T1) for carbonyl carbons in a variety of oils and fats had been obtained and analyzed comprehensively. With this set of acquisition parameters and free induction decay (FID) data processing method, error of less than 2.0 mol% were obtained with high repeatability and versatility for the analysis of oils and fats from diverse sources, including the reaction intermediates by chemical interesterification, lipids content extracted from biological samples and those natural occurring oils without their regiospecific data reported up-to-date. Instead of the semi-quantitative approach in previous reports on fish oil, we used narrower spectral width targeting sn-position in triacylglycerols to obtain full quantitative data in a shorter analysis time. The present selection of data acquisition and processing parameters led to a blueprint for a generic approach to performing a routinely practiced qCNMR regiospecific analysis.